Freight Forwarder's Intermediary Role in Multimodal Transport Chains : A Social Network Approach - Schramm, Hans-Joachim, (Writer on freight and freightage) (Contributions to management science, 2012)
• 520 In this book, the business of international freight forwarding is examined from both a theoretical and empirical point of view with a special emphasis on multimodal transport chains, including sea or air transport operations. In such contexts, the freight forwarder is always considered "The Architect of Transport", but this intermediary role seems to be largely neglected in research to date. Therefore, relevant concepts from economic theory and economic sociology are employed to produce both an intermediary and a network perspective of freight forwarding in order to provide a better understanding of this kind of transportation business. Furthermore, its intermediary role in such inherent network structures is explored by mapping relationship patterns in a stylized model framework applied to a questionnaire-based sample collected among freight forwarders engaged in such multimodal transport chains in Germany (especially from Hamburg, Bremen and Bremerhaven) as well as in Austria in 2003